Challenges for Spain form the jihadi terrorism. The impact of the Islamic State = Wyzwania dla bezpieczeństwa Hiszpanii ze strony dżihadyzmu w kontekście oddziaływania Państwa Islamskiego - Kosmynka, Stanisław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The rise of the Islamic State has created a new, very serious dimension of the threat from the global jihadi movement. The sense of duty and belonging to a kind of transnational organization are some crucial aspects of the jihadists` identity. The paper seeks to understand the challenges for the Spanish security generated by Muslim volunteers from this country travelling to Syria and Iraq who are in-volved in terrorist and violent actions.
Keywords: terrorism; jihadism; Islamie State; Spain; security; radicalization; terroryzm; dżihadyzm; Państwo Islamskie; Hiszpania; bezpieczeństwo; radykalizacja